A Brief Review on Cross-linking in Hydrogel - Jaya Maitra (Research Aspects in Chemical and Materials Sciences Vol. 3, 2022)
In polymer chemistry, cross-linking is a stabilising procedure that results in the multidimensional extension of the polymeric chain and network structure. A cross-link is a bond that connects two polymer chains. It could be covalent or ionic. By limiting movement, cross linking turns a liquid polymer into a "solid" or "gel." Polymer chains lose some of their capacity to move independently when they are connected by cross-links. Hydrogels are a type of polymer with a high water content that has physical or chemical crosslinks. By cross-linking the chains, a liquid polymer (where the chains are free to flow) can be transformed into a "solid" or "gel." A polymer with cross linking has a larger molecular mass. Because they are mechanically robust and resistant to heat, wear, and solvent attack, cross-linked polymers are significant. Cross-linked polymers have the disadvantage of being insoluble and infusible, which makes them relatively rigid in terms of processing characteristics.